Seasonal Mean Variability of Coral-based Sea Surface Salinity from Simeulue, Mentawai, Bunaken, and Bali - Sri Yudawati Cahyarini (Geological Agency, 2013)
DOI: 10.17014/ijog.v8i3.161Sea surface salinity is an important parameter in a climate study. Coral δ18O records δ18O seawater and sea surface temperature (SST). While, coral Sr/Ca records SST only commonly used in a paleoclimate study to reconstruct SST. Thus, paired coral δ18O and Sr/Ca can be used to reconstruct δ18O seawater. δ18O seawater and SSS is linearly correlated, thus reconstructed δ18O seawater further is used to reconstruct sea surface salinity (SSS). Instead of using coral Sr/Ca as SST recorder, paired model (grid) or measured SST data is used to reconstruct SSS. In this study, paired coral δ18O and grid SST data are presented to reconstruct SSS from several different locations across Indonesian sea i.e Simeulue, Mentawai, Bunaken, and Bali. Coral-based SSS reconstructions from those locations are then compared to the grid SSS in the seasonal mean scale. The result shows that annual mean variation of salinity for period of 1958-2008 in Mentawai and Simeulue is 33.25 psu and 33.26 psu respectively, while in Bunaken and Bali is 34.03 psu and 33.47 psu respectively. Correlation coefficient between coral salinity and salinity from model data in the seasonal/monthly mean scale is high i.e R = 0.62 - 0.83. Based on the monthly mean data, corals in the studied area strongly record SSS variation in the monthly or seasonal mean scale. In Mentawai and Simeulue waters, SSS variation is influenced strongly by monsoon. While, in addition to the monsoon, ocean advection also affects seasonal variability of SSS in the Bunaken and Bali waters.